2013
DOI: 10.1002/anie.201302315
|View full text |Cite|
|
Sign up to set email alerts
|

Chemical Activity of Thin Oxide Layers: Strong Interactions with the Support Yield a New Thin‐Film Phase of ZnO

Abstract: It has been pointed out to the authors that there is at ypographical error in the theoretical part of the experimental section of the original Communication. Specifically, the metal supercell used in the theoretical calculations was 5 ” 5i nstead of the published 4 ” 4. The resulting simulation cell was thus a4” 4(bi-)layer of ZnO on 2 layers of 5 ” 5C u(111). As also later pointed out by Bieniek et al. [1] this yields alattice mismatch between the two materials of only ca. 1% in order to strain the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
173
5
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(200 citation statements)
references
References 36 publications
17
173
5
5
Order By: Relevance
“…However, our studies of FeO(111) [10] and ZnO(0001) [13] films on Pt(111) showed that such a monolayer structure is unstable under realistic pressure conditions. Moreover, other DFT studies of ZnO(0001) films on noble metals (Pd(111) [35], Cu(111) [36], and Au(111) [37]) and experimental data available for ZnO/Ag(111) [21] revealed substantial interlayer relaxations such that ultrathin ZnO films resemble the co-planar sheets in the boron nitride (or graphite) structure, and they are only weakly bound to a metal support, in contrast to the models used by Sun et al [34].…”
Section: Reactivity Of Metal-supported Zno(0001) Films: Comparisonmentioning
confidence: 99%
“…However, our studies of FeO(111) [10] and ZnO(0001) [13] films on Pt(111) showed that such a monolayer structure is unstable under realistic pressure conditions. Moreover, other DFT studies of ZnO(0001) films on noble metals (Pd(111) [35], Cu(111) [36], and Au(111) [37]) and experimental data available for ZnO/Ag(111) [21] revealed substantial interlayer relaxations such that ultrathin ZnO films resemble the co-planar sheets in the boron nitride (or graphite) structure, and they are only weakly bound to a metal support, in contrast to the models used by Sun et al [34].…”
Section: Reactivity Of Metal-supported Zno(0001) Films: Comparisonmentioning
confidence: 99%
“…15 The formation of the graphitic-like ZnO overlayer with hexagonal BN structure (h-BN) on Cu has been reported by Lunkenbein et al 16 as the consequence of strong metal support interaction (SMSI) on real Cu/ZnO/Al2O3 catalysts. To this end, high-resolution electron microscopy images have been reported.…”
Section: Introductionmentioning
confidence: 90%
“…a From ref. 15 We consider now CO adsorption on ZnO/Ag(111). We notice only very minor changes going from the unsupported to the supported oxide film, see Table 3 and 4.…”
Section: Co Zno Wurtzite and Unsupported Graphitic Zno Bilayermentioning
confidence: 99%
See 2 more Smart Citations